The impact of specific motoricity on karate performance in young karateka - Katić, Ratko (Array, 2009)
Abstract: The aim of the study was to assess interdependence of specific motor abilities (situation karate tests) and motor skills (karate techniques), and karate performance (fighting efficiency) in under-sixteen male karateka aged 11–12 and 13–14 years. A battery of 5 situation motor tests were applied and 6 basic elements of karate technique evaluated in a sample of 20 male karateka aged 11–12 and 20 male karateka aged 13–14 years. Three criterion variables were formed: 1) one factor as a factor of general technical efficiency in karate was isolated by factor analysis of 6 karate techniques; 2) cumulative evaluation of 2 kate as kate performance; and 3) total score assessment based on success achieved at national karate championships as contest efficiency (fighting efficiency). Regression analysis revealed the frequency of gedan barai blockade performance to be the superior predictor of technical efficiency, kate performance and contest success in karateka aged 11–12, whereas the speed of the gedan barai-jaku zuki (block-kick) combination performance and specific agility (sidewise mobility) were superior predictors of performance in karateka aged 13–14. Of the karate techniques (kicks) used, the quality of jaku zuki kick performance was the superior predictor of contest efficiency in karateka aged 11–12, and the quality of the jaku zuki-mawashi geri and kizame zuki-jaku zuki combination performance in karateka aged 13–14